Applications of ESEM on Materials Science: Recent Updates and a Look Forward. Issue 2 (4th December 2019) - Zhang, Zhouyang; Zhou, Yangbo; Zhu, Xinli; Fei, Linfeng; Huang, Haitao; Wang, Yu
Abstract: The microscopic understanding of materials relies on the development of microscopy. Historically, the technological evolution from optical microscopes to electron microscopes has directly stimulated many discoveries of new physical and chemical fundamentals as well as advanced materials. Scanning electron microscopy (SEM) is, undoubtedly, the most widely used tool for microscopic characterization in modern materials science. Especially, the incorporation of a gas pressure around the sample area of conventional SEM, i.e., the environmental scanning electron microscope (ESEM), has opened new possibilities in observing samples in their natural states, leading to unprecedented chances for studying the details of biological, organic, and hydrated samples. What is more, in recent years, in situ ESEM studies concerning materials change and chemical reactions have played a more important role in the field of materials science. Herein, the recent applications of ESEM in materials science are comprehensively reviewed, in terms of common static observations for various materials and in situ investigations of dynamic processes in controlled experimental environments. Moreover, the problems concerning state‐of‐the‐art ESEM experiments are discussed, as well as possible solutions. Looking forward, the rapid developments on instrumentation and fundamental science of ESEM can bring a clear vision of materials in the near future. Abstract : The application of environmental scanning electron microscope (ESEM) in the field of materials science has greatly expanded in the past two decades. Herein, the significant contributions brought by ESEM for static and in situ observations on materials (especially for insulated/wet samples) are reviewed, with an emphasis on the potential of ESEM observations in the future development of materials science.